Implementation of Office Administration Practice Media to Welcome the Independent Curriculum - Suputra, I Nyoman; Basuki, Andi; Dharma, Buyung Adi; Sakdiyyah, Dewi Ayu (PT. Riset Press International, 2023)
This study aims to produce office administration practice media to welcome the independent curriculum. The learning media includes petty cash management, archive management, writing letters and preparing a leader's activity schedule which will be developed in one integrated application. The design of this study adopts the Borg and Gall model which consists of 10 stages. This research was conducted in Malang City at the Office Management and Business Service Vocational High School. The test subjects involved 20 students in the small group trial and 50 students in the large group trial. This research activity also involved material expert valiators and media experts to determine the feasibility and validity of the product being developed. The results of this research and development are learning media called SIRAKA which are feasible and valid to be applied in the learning process of managing office administration practices. This is based on the results of small group trials which obtained an average of 88% and large group trials obtained an average of 90%. While the results of the material expert validator and media expert obtained an average score of 89%. So it can be concluded that SIRAKA learning media can be used as an alternative media for the practice of managing office administration in the Department of Office Management and Business Services